STRATEGI AFEKTIF DALAM MENGATASI PERMASALAHAN PEMALU PADA AUD: FAKTOR PENYEBAB, PENDEKATAN, DAN DAMPAK PSIKOSOSIAL - Rizky Aprilia Pratiwi; Ulwan Syafrudin; Renti Oktaria (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
The problem of shyness in early childhood cannot be left alone because it will affect their personality. This research aims to find out about effective strategies for overcoming shyness problems, namely including the causal factors, approaches used in overcoming shyness problems, and the psychosocial impact on AUD. This research uses a qualitative case study type approach. Data collection techniques use interviews, observation and documentation. The main subject of the research was an 8-year-old child in Tanjung Selamat subdistrict, Bandar Lampung city. Data analysis using Miles and Huberman. The results of this research found that the factors that cause shyness problems in children consist of internal factors and external factors. The approach used is a psychological intervention which focuses on developing social skills and increasing self-confidence, such as parents taking their children out of the house to interact with neighbours, introducing children to children their age, role-playing, and encouraging children to play with friends outside the home. , and limit children's use of cell phones so that children do not enjoy being alone. The psychosocial impacts of shy children that researchers found included the impact on social interactions and lack of managing emotions.